Ichthyofauna of the Ribeirao Frutal and tributaries, upper Rio Parana basin, Minas Gerais, Southeastern Brazil - Azevedo-Santos, Valter M. [UNESP]; Coelho, Paula N. [UNESP]; Depra, Gabriel de Carvalho (Revista Biota Neotropica, 2018)
The Ribeirao Frutal basin is located within the upper Rio Parana system, in the Frutal municipality, Minas Gerais State, Southeastern Brazil. Until now, there was no complete ichthyological survey published for this small basin. Therefore, here we provided a list of fish species from the Ribeirao Frutal and some of its tributaries. We found 31 species of fishes representing five orders and ten families. We identify a likely undescribed and five non-native species in the Frutal basin. Lastly, we recommend new surveys of fishes in small hydrographic basins within upper Rio Parana system.
Keywords: Ichthyology; inventory; Neotropical region; Rio Grande; survey